Nasal high flow oxygen therapy after extubation: the road is open but don’t drive too fast! - Rabbat, Antoine; Blanc, Kim; Lefebvre, Aurélie; Lorut, Christine (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Mechanical ventilation (MV) is necessary for many patients admitted in intensive care unit (ICU). In intubated patients, weaning from invasive MV is a major event during their ICU stay (1,2). Delayed extubation increases the risks associated with IMV and extubation failure is associated with prolonged ICU and hospital stays and increased mortality, particularly attributable to nosocomial infection (3-5).